Kerajinan Anyaman Bambu Di Sanggar Kreatif “Bunga Matahari” Kelurahan Rambung Barat Kecamatan Binjai Selatan - Latifah Hanum Rusdi; Heri Soeprayogi; Mesra Mesra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This research aims to "know the manufacturing process, applied motifs, and colors used in bamboo woven crafts products". The method of research done is a descriptive method. Samples are used only 5 types of products, of each 5 of these types are taken 2 samples of the product. Up to 10 total samples. The population in this study totaled about 1 million products from 15 product types produced. Data collection techniques using observation techniques, interviews, and documentation. The results of this research show that the process of making crafts woven bamboo in Sanggar creative "Sunflower" Village Rambung Barat, District South Binjai in the outline has 4 stages, namely the provision of tools and materials, processing of raw materials, process of workmanship, and finishing process. Motif applied to the handicrafts woven bamboo is a motif of a single base (sasaq), a motif of the double basic woven (braid), and hero eye motif. The color used in bamboo woven crafts are bamboo color (basic natural color), red color (primary color), green color (secondary color), a combination of red and green color (complementary color), as well as black color (the color is produced from mixing thinner and grand flour).